Women Judges in the Muslim World A Comparative Study of Discourse and Practice - Lindbekk, Monika; Sonneveld, Nadia (Brill, 2020)
Women Judges in the Muslim World: A Comparative Study of Discourse and Practice fills a gap in academic scholarship by examining public debates and judicial practices surrounding the performance of women as judges in eight Muslim-majority countries (Indonesia, Malaysia, Pakistan, Syria, Egypt, Libya, Tunisia and Morocco). Gender, class, and ethnic biases are inscribed in laws, particularly in the domain of shariʿa-derived family law. Editors Nadia Sonneveld and Monika Lindbekk have carefully woven together the extensive fieldwork and expertise of each author. The result is a rich tapestry that brings out the various effects of women judges in the management of justice. In contrast to early scholarship, they convincingly prove that 'the woman judge' does not exist.